2008
DOI: 10.1042/bj20081403
|View full text |Cite
|
Sign up to set email alerts
|

Structural requirements of KTS-disintegrins for inhibition of α1β1 integrin

Abstract: Obtustatin and viperistatin represent the shortest known snake venom monomeric disintegrins. In the present study, we have produced recombinant full-length wild-type and site-directed mutants of obtustatin to assess the role of the K(21)TS(23) tripeptide and C-terminal residues for specific inhibition of the alpha(1)beta(1) integrin. Thr(22) appeared to be the most critical residue for disintegrin activity, whereas substitution of the flanking lysine or serine residues for alanine resulted in a less pronounced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 39 publications
5
24
0
Order By: Relevance
“…When their second subunit contains RGD, they bind to α 5 β 1 integrin [184]. Disintegrins with KTS/RTS motif bind to α 1 β 1 integrin [135,185,186,187,188,189]. The selectivity and potency strongly depends on the amino acid composition surrounding RGD/MLD/KTS/RTS motifs.…”
Section: Svmps As Research Tools and Diagnostic And Therapeutic mentioning
confidence: 99%
“…When their second subunit contains RGD, they bind to α 5 β 1 integrin [184]. Disintegrins with KTS/RTS motif bind to α 1 β 1 integrin [135,185,186,187,188,189]. The selectivity and potency strongly depends on the amino acid composition surrounding RGD/MLD/KTS/RTS motifs.…”
Section: Svmps As Research Tools and Diagnostic And Therapeutic mentioning
confidence: 99%
“…The threonine present in the tripeptide KTS of the disintegrin obtustatin is key for the binding to a 1 b 1 integrin [40]. It has been suggested that the RTS/KTS short disintegrins may have been recruited into the venom gland of Eurasian vipers independently of the canonical neofunctionalization pathway characteristic of the RGD disintegrins [41].…”
Section: Introductionmentioning
confidence: 99%
“…Dimeric disintegrins exhibit the largest variability in their integrin recognition motifs, including MLD (in addition to RGD and KGD), which targets the a 4 b 1 , a 4 b 7 , a 3 b 1 , a 6 b 1 , a 7 b 1 and a 9 b 1 integrins; VGD and MGD, which impair the function of the a 5 b 1 integrin; and WGD, a potent inhibitor of the RGD-dependent integrins a 5 b 1 , a v b 3 , and a IIb b 3 [25,26]. KTS and RTS motifs have been found in short disintegrins, which selectively target the integrin a 1 b 1 [29,30] and form a distinct clade of recently evolved short disintegrins [31].…”
Section: Introductionmentioning
confidence: 99%